New insights into in vitro amyloidogenic properties of human serum albumin suggest considerations for therapeutic precautions - Sharma, Neetu; Sivalingam, Vishwanath; Maurya, Sonalika; Prasad, Archana; Khandelwal, Puneet; Yadav, Subhash Chandra; Patel, Basant K. (Febs Letters, 2015)
Amyloid aggregates display striking features of detergent stability and self-seeding. Human serum albumin (HSA), a preferred drug-carrier molecule, can also aggregate in vitro. So far, key amyloid properties of stability against ionic detergents and self-seeding, are unclear for HSA aggregates. Precautions against amyloid contamination would be required if HSA aggregates were self-seeding. Here, we show that HSA aggregates display detergent sarkosyl stability and have self-seeding potential. HSA dimer is preferable for clinical applications due to its longer retention in circulation and lesser oedema owing to its larger molecular size. Here, HSA was homodimerized via free cysteine-34, without any potentially immunogenic cross-linkers that are usually pre-requisite for homodimerization. Alike the monomer, HSA dimers also aggregated as amyloid, necessitating precautions while using for therapeutics. (C) 2015 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Drug carrier; HSA amyloid; Plasma expander; Sarkosyl; Self-seeding